Lifestyle clusters and academic achievement in Australian Indigenous children: Empirical findings and discussion of ecological levers for closing the gap. (April 2020) - Wilson, Rachel; Dumuid, Dorothea; Olds, Tim; Evans, John
Abstract: Participation in sport and physical activity can improve academic outcomes and has been identified as a potential mechanism for addressing educational disadvantage and 'closing the gap' in Australian Indigenous communities. To explore this possibility in relation to sport and lifestyle we performed a cluster analysis on data from the Footprints in Time study (also known as the Longitudinal Study of Indigenous Children), using data from Waves 3–6 (2010–2013, ages 5–9 years) of this cohort study. Cluster inputs were organised according to not only sports participation, but also screen time, sleep duration and unhealthy food intake, as reported in parent surveys. Associations between lifestyle cluster membership and academic outcomes from standardised tests from 2014-5 (Progressive Achievement Tests [PATs] for Maths and Reading, and National Assessment Program for Literacy and Numeracy [NAPLAN]) were examined using linear models. Analyses were adjusted for age, sex, remoteness and parental education. Three clusters were identified: Low Sport (36% of sample), characterised by low sports participation and low sleep duration; Junk Food Screenies (21% of sample), with high screen time and high intake of unhealthy foods; and High Sport (43% of sample), showing high sports participation and low screen time. Cluster membership was associated with academic performance for NAPLAN Literacy and Numeracy, and for PAT Maths. The High Sport cluster consistently performed better on these tests, with effect sizes (standardised mean differences) ranging from 0.10 to 0.38. We discuss the ecological dynamics potentially contributing to lifestyle cluster membership and ways in which policy can support healthier High Sport lifestyles associated with better academic performance. Highlights: Sport holds cultural significance in Indigenous communities. Few data relating to sport and lifestyle outcomes within these communities have been examined. Sport participation varies among lifestyle clusters:  Low Sport  (36%),   Junk Food Screenies  (21%),   High Sport  (43%). The  High Sport  cluster performed consistently better on literacy and numeracy tests. Ecological Systems Theory is used to consider ways to improve sport participation, lifestyles and education outcomes.